Public Policy-Making - Anderson, James E. (New York : Praeger Publisgers, 1975)
This book is one of a series of volumes, published and forthcoming, written for introductory and intermediate undergraduate courses in political science. Second, it raises some basic methodological issues involved in studying politics. Third, it introduces the student to concrete aspects of political activity through the use of unifying concepts that cut across both traditional subfields of the discipline and formal institutions, or structures of government. Fourth, it attempts to overcome the student's natural parochialism.
Includes index.
Includes bibliographical references: p. 169-173.
ne 7/06/2018
Loans
Keywords: Policy sciences; United States